PENGARUH PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN RUMPUT ODOT (PENNISETUM PURPUREUM CV. MOTT) - Iqbal Permana Ginting; Meriksa Sembiring (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the effect of appropriate urea fertilizer on the growth of odot grass (Pennisetum purpureum). This study used a non-factorial Randomized Block Design (CRD) consisting of 4 treatments and 6 replications. The treatments given were:P0 = Without urea fertilizer (control), P1 = Urea fertilizer 5 grams/100 ml of water/plant, P2 = Urea fertilizer 10 grams/100 ml of water/plant, P3 = Urea fertilizer 15 grams/100 ml of water/plant. The response of Odot grass to several concentrations of urea fertilizer by dissolving urea fertilizer in 100 ml of water that was watered for each treatment and with each treatment dose. Fertilization was carried out 2 times until harvest at one week after planting and 3 weeks after planting (wap). The parameters observed were height growth, stem diameter, number of tillers and fresh forage production. Observations for grass height at 2, 4, and 6 weeks after planting, while for the number of tillers and stem diameter were carried out before harvest (40 days after planting) and fresh forage production was carried out at harvest by weighing each different plot after cutting. Data from the research results were analyzed statistically, if the test was significantly different and continued with testing using DMRT.The results of the research from the data that had been analyzed against the observed parameters from the influence of several concentrations of urea fertilizer use were significantly different (p <0.05), with the results that the higher the concentration of urea fertilizer used, the higher the growth and fresh production.